PERLAWANAN PEREMPUAN TERHADAP BUDAYA PATRIARKI DALAM CERPEN-CERPEN KALIMANTAN TIMUR - Diyan Kurniawati (Kantor Bahasa Kalimantan Timur, 2019)
This paper discusses the resistance of women in relation to gender relations in short stories of East Kailimantan. With gender theory and supported identity theory, this study analyzes the process of women’s resistance to counter patriarchal culture. Analysis is done by examining the way women do resistance to patriarchal culture. The interactionof women with other individuals will also be analyzed to find out the infinity as a positive or negative factor for women. Analysis shows the formof resistance is done by means of violenceor not. Violently, resistance is done by removing patriarchal cultural icons. Resistance is also done by choosing identity different from previous identity. Analysis also shows the process of such resistance can cause identity conflicts with oneself. Resistance is not always succesful. Short stories East Kalimantan show complicated situation make women can not fully escape from patriarchal culture.